Varicella antibody in healthy children - Sri Rezeki Hadinegoro (Indonesian Pediatric Society, 1999)
Varicella is the most contagious viral exanthematous disease, which has a variable clinical course. We studied a seroepiderniologicaJ study on varicella antibody in 350 healthy children at Department of Child Health, Medical School, University of Indonesia, Dr. Cipto Mangunkusumo Hospital, Jakarta; from May to July 1998. The aim of this study was to get figures of varicella antibody in healthy chiJdren which can be used as a baseline data in the decision of recommendation in varicella vaccination. Subjects were 1-12 years old children with no history of varicella infection or immunization. The varicella antibody was determined by using Etisa assay (Enzygnost lest). Among 350 healthy children, 42.9% were males; they were divided into 3 age groups: 1-3, 4-7 and 8-12 years. Fourty two children (11.1 %) had seropositive varicella antibody (above protective level 0.2 mIU/ml). The prevalence of subclinical valicella significance increased with increasing age. Subjects with clinical or subclinical varicella had the same figure of age specific prevalence. The mean varicella antibody in each age group was almost similar. The minimum varicella antibody titer was quite similar between 1-3 and 4-7 age group, but not in 8-12 age group. Forty one percent had history of varicella contact, older chiildren had more history of contact.